EPISTEMIC ARCHITECTURE OF SECURITY: PHILOSOPHICAL AND METHODOLOGICAL FOUNDATIONS FOR RESEARCHING INFORMATION AND COGNITIVE SECURITY IN THE CONDITIONS OF CYBER-SOCIETY - Khrystokin, Hennadii; Verkhovtseva, Iryna; Marutian , Rena (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
Introduction. The question of what exactly is being protected in information security has ceased to be purely rhetorical. Russia's full-scale aggression against Ukraine demonstrated that the most vulnerable object of attack is not infrastructure, but society's ability to distinguish real from constructed. This article develops the concept of structural correlation of rationalities proposed in a preceding study (Khrystokin, Verkhovtseva, and Slyusar 2025). The aim and tasks. The article aims to substantiate the concept of epistemic architecture of security as a philosophical and methodological framework for analysing information and cognitive security in cyber society and to show how artificial intelligence transforms threats to this architecture. Research methods. The study draws on Stepin's typology of scientific rationality, Longino's social epistemology, Habermas's theory of communicative action, as well as Foucault's concept of regimes of truth, Floridi's concept of the infosphere, and Gillespie's analysis of platform architectures as epistemic actors. Research results. The epistemic architecture of security is a four-pole structure whose dimensions – verificational, communicative, narrative, and identificational – stand in a necessary mutual dependency. The verificational dimension addresses the establishment of facts. The communicative dimension concerns the architecture of information flows and their distribution across audiences. The narrative dimension governs the interpretation of events. The identificational dimension encompasses cognitive biases and identity processes that enable manipulation. Artificial intelligence is analysed as an actor that attacks all four dimensions simultaneously. The concept of epistemic resilience is introduced as the society's capacity to restore the integrity of this architecture after an attack. Conclusions. Epistemic resilience is a systemic property of the interaction between institutions, social practices, and individual skills. The concept of epistemic architecture of security develops the structural correlation of rationalities proposed in the preceding study, transferring it from the level of scientific cognition to the level of public cognition and providing both a diagnosis of vulnerability and a criterion for its restoration.